INFLUENCE TWO CIRCULAR HOLES WICH COVER AGAIN ON CONCENTRATION OF STRESSES IN INFINITE PLATE BY DISPLACEMENT - Пономаренко, Олександр Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper is devoted to the investigation influence two circular holes wich cover again on concentration of stresses in infinite plate by displacement. The analysis is developed on the basis of the Airy`s stresses function in generalized plane stresses and by applying bipolar coordinates.